New and rare echiurids of the family Bonelliidae - Murina, G. -W. W. (Trudy Instituta Okeanologii, 1978)
А new genus апd 5 пеw species of Bonelliidae were established and described. The material was collected in western апd southern parts of the Pacific during the expeditions of r/v «Vityaz» and «Mendeleev» in 1975–1976, including the Philippeen, Mariana and Riu-Kiu trenches. А new monotypical genus Zenkevitchiola was established (оn the species Z. brevirostris). Besides it 3 new species were described: Choanostomella vinogradovae, Sluiterina album and Vityazema planirostris. The spatial distribution of some old species was dilated: Torbenwolffia galatheae, Pseudoikedella achaeta and Hamingia arctica.
In Russian with English summary